(Trans)dermal film-forming systems: challenges in design and characterization of an innovative product - Pantelić, Ivana (Archives of Pharmacy, 2022)
Topical route of drug application offers a range of possibilities, but often with poor patient adherence. Development of formulations that form a discrete film upon application compiles the advantages of (trans)dermal patches and conventional liquid or semisolid topical dosage forms, leading to efficient drug penetration with less frequent use. However, development and characterization of these systems is challenging, and the current draft guideline of the European Medicines Agency (EMA) has opened additional questions. Optimal selection of film-forming polymers (often from the groups of vinyl alcohols, silicones or methacrylates), volatile and non-volatile solvents, plasticizers and/or penetration enhancers, usually requires assistance of an experimental design, along with a holistic QbD concept. Active pharmaceutical ingredient’s (API) solubility must be sufficient in both volatile and non-volatile excipients, leading to its transient supersaturation, without crystallization. Thus, non-volatile excipients generate a matrix film structure that enhances drug delivery into deeper skin layers, without compromising skin barrier integrity. Undoubtedly, when aiming for transdermal delivery, the API itself must meet certain requirements (logP=1-3, MW